2020
DOI: 10.21577/0103-5053.20200063
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Selective Fluorescent Chemosensor for Al3+ Based on 2,2’:6’,2”-Terpyridine with a Salicylal Schiff Base

Abstract: Two 2,2':6',2"-terpyridine-based Schiff bases (TPySSB and TPySB) have been synthesized. The TPySSB shows remarkable selective 'off-on' fluorescence for Al 3+ in combination with photoinduced electron transfer (PET) mechanism and C=N isomerization mechanism. Chemosensor TPySSB binds Al 3+ in a 1:2 ratio with an association constant 6.8 × 10 5 (correlation coefficient (R 2) = 0.98) and this 1:2 stoichiometric model is established on Job's plot and 1 H nuclear magnetic resonance (NMR). Comparing TPySSB and TPySB,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Both absorption spectral titrations demonstrate the sensitivity of the CuCl 2 L receptor towards minute changes in Cys and His concentrations. The detection limits [92][93][94] for Cys and His were calculated to be 0.33 μM and 1.40 μM, respectively, indicating the high sensitivity of the CuCl 2 L receptor for these analytes. The linear relationships To assess the selectivity of our receptor towards Cys, we conducted competition experiments, whose results are shown in Fig.…”
Section: In the Esi †)mentioning
confidence: 99%
“…Both absorption spectral titrations demonstrate the sensitivity of the CuCl 2 L receptor towards minute changes in Cys and His concentrations. The detection limits [92][93][94] for Cys and His were calculated to be 0.33 μM and 1.40 μM, respectively, indicating the high sensitivity of the CuCl 2 L receptor for these analytes. The linear relationships To assess the selectivity of our receptor towards Cys, we conducted competition experiments, whose results are shown in Fig.…”
Section: In the Esi †)mentioning
confidence: 99%
“…A condensation reaction between 4 0 -amine-2,2 0 6 0 2″-terpyridine with benzaldehyde derivatives resulted in the synthesis of Schiff bases (Figure 45) which were studied for its cation recognition properties for various ions. It was observed that the synthesized Schiff bases selectively recognized Al +3 ions due to enhancement in fluorescence [72].…”
Section: Role Of Schiff Bases In Ion Recognitionmentioning
confidence: 99%
“…Comparatively, optical detection such as the uorescence method shows unique potential for high sensitivity. 19 At present, uorescent chemosensors have been widely used to detect different metal ions because of their high sensitivity, selectivity, and fast response time, 20,21 including to detect a trace of Al 3+ ions. Therefore, the development of an analytical method of Al 3+ ions based on uorescence detection is still interesting, in particular, to solve the issues of weak coordination ability of Al 3+ ions and its lack of spectroscopic characteristics.…”
Section: Introductionmentioning
confidence: 99%